Wettability and morphological characterization of a polymeric bacterial cellulose/corn starch membrane - Da Silva, Carina Maiara; Bottene, Marcia Karspinki; De Oliveira Barud, Hélida Gomes [UNESP]; Da Silva Barud, Hernane [UNESP]; Ligabue, Rosane Angélica; Jahno, Vanusca Dalosto (FapUNIFESP (SciELO), 2015)
The uses of polymer blends have stimulated research to promote a better performance of existing raw materials. The implementation of blends in the production of polymeric membranes has shown great results in regenerative medicine and consequently it has improved the application of biomaterials in this area. This study aimed to evaluate the morphology and wettability of a bacterial cellulose/corn starch polymeric membrane. In relation to biomaterials, wettability is an important property to be evaluated because it is possible to observe if the degradation is accelerated even when in contact with biological fluids. The membrane was morphologically evaluated by SEM. Results showed that there was interaction between the polymers. Additionally, by the technique of contact angle it was also possible to observe the ability to absorb water, being highly satisfactory, showing a complete wetting with a contact angle of 10.7° in the initial assessment and 6.6° in the evaluation after 5 seconds.
Keywords: Bacterial cellulose; Biomaterial; Blends; Corn starch; Membrane